2017
DOI: 10.1111/jce.13190
|View full text |Cite
|
Sign up to set email alerts
|

Recurrences in the Blanking Period and 12‐Month Success Rate by Continuous Cardiac Monitoring After Cryoablation of Paroxysmal and Non‐Paroxysmal Atrial Fibrillation

Abstract: CB-PVI for paroxysmal AF shows a 12-month success rate of 76.5% after one single procedure, as assessed by continuous cardiac rhythm monitoring. Within-blanking recurrences predict the ablation failure in more than 80% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
21
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 40 publications
5
21
1
3
Order By: Relevance
“…A recent study investigating the use of internal loop recorder for more precise determination of the success of PVI by CB ablation, in which 98.3% of the patients had undergone ablation using CB2, has reported that early recurrence occurred in 28.3% of patients ( n = 17), out of whom 14 (82.3%) had also late recurrences . In this study, late recurrence rate was 55% . These data suggest that subclinical recurrence rates are actually higher than clinically reported rates when compared to several single‐center‐based studies.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…A recent study investigating the use of internal loop recorder for more precise determination of the success of PVI by CB ablation, in which 98.3% of the patients had undergone ablation using CB2, has reported that early recurrence occurred in 28.3% of patients ( n = 17), out of whom 14 (82.3%) had also late recurrences . In this study, late recurrence rate was 55% . These data suggest that subclinical recurrence rates are actually higher than clinically reported rates when compared to several single‐center‐based studies.…”
Section: Discussionmentioning
confidence: 42%
“…It is of note that the majority of studies evaluating the efficacy of CB ablation for AF have used 24‐h ECG Holter monitorization during follow‐up visits. A recent study investigating the use of internal loop recorder for more precise determination of the success of PVI by CB ablation, in which 98.3% of the patients had undergone ablation using CB2, has reported that early recurrence occurred in 28.3% of patients ( n = 17), out of whom 14 (82.3%) had also late recurrences . In this study, late recurrence rate was 55% .…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Mugnai et al found that ER was independently associated with LR (HR = 6.79) [ 22 ]. Moreover, Pieragnoli et al demonstrated that 82.3% of patients with ER after RFCA experienced LR, whereas only 30.2% of patients without ER experienced LR [ 23 ]. Yalin et al found that arrhythmia recurrence during the blanking period was an independent predictor of long-term AF recurrence, although the treatment was not RFCA but second-generation cryoballoon [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of JCE, Pieragnoli et al add to this evolving literature by reporting their experience with recurrences during the blanking period after cryoballoon ablation for AF. 11 They followed a small patient population of both paroxysmal and nonparoxysmal AF patients.…”
mentioning
confidence: 99%